The utilization of Technological Pedagogical Content Knowledge (TPACK) in elementary school learning - Filina, Nurul Zikri; Sari, Siti Mayang; Zahraini, Zahraini (IJBLE Scientific Publications Community Inc., 2024)
This research aims to explore the use of Technological Pedagogical Content Knowledge (TPACK) in the learning context at the elementary school level. The research approach applied was qualitative with a focus on case studies at SD Negeri 16 Banda Aceh, class 4. Data collection was carried out through classroom observations, interviews and document analysis. The research results show that the integration of TPACK in learning in elementary schools has a positive impact. Teachers have succeeded in integrating information and communication technology (ICT) well in planning and implementing learning. They use various ICT tools and applications that are appropriate to the learning content as well as effective teaching strategies. In addition, teachers are also able to apply pedagogical and content knowledge effectively to facilitate interesting and meaningful learning for students. There are several challenges faced by teachers in implementing TPACK. Some obstacles include limited access to ICT devices and resources, lack of training capable of developing TPACK competencies, as well as obstacles in integrating TPACK into the existing elementary school curriculum. The findings of this research provide a deeper understanding of the use of TPACK in learning at the elementary school level. The implications of this research can be the basis for developing teaching materials and educational policies that support the integration of TPACK in the learning process in elementary schools.